Status of sand mining and quality in northern Kathmandu, Central Nepal - Sayami, Mamata; Tamrakar, Naresh Kazi (Bulletin of the Department of Geology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Growing trend of urbanization in Kathmandu has increased the demands of sand for building materials of concrete. Demand of sand has been fulfilled from terrace and riverbed mining in northern region of Kathmandu and by importing from west of Kathmandu. Riverbed excavation and some quarries in terrace deposits are illegally operated. Although riverbed excavation is prohibited, majority of the sand comes from such mining. Questionnaire analysis, analysis of secondary data and sand samples were carried out in laboratory to obtain (a) the existing status of sand mining and (b) the quality of sand supplied to the market. About 60% demand of sands have been fulfilled through riverbeds while 40% have been fulfilled through terrace deposits. The Sanla and the Manahara Rivers have been the most efficiently excavated rivers. About 1865 m3 sands from river and 1238 m3 from terraces have been excavated per day. Future demand of sand may increase considering 60% increase of household in the valley. Out of total excavation sites in the valley, 40% illegal sites are located in rivers and 5% in terrace deposits. Mining policy and laws are weak to control illegal mining and to bring miners and dwellers into the framework of taxation. The river or terrace sands do not differ much in major constituents, but the former sands are more matured. Both sands are hazardous in terms of mica content that approaches 10 to 32% lying beyond the acceptable limit of 8%. Other deleterious materials are quite low in percentage and do not exceed 3%. If processing can be applied to reduce mica content at a commercial-scale, the sands in the Kathmandu Valley will be probably of good quality. doi: 10.3126/bdg.v10i0.1424 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 10, 2007, pp.89-98